Community Structure and Driving Factors for Rhizosphere Ectomycorrhizal Fungi of Pinus Massoniana L. In Yuntai Mountain - Zhang, Wenquan; Xie, Dashi; Yu, Huafang; Deng, Jie; Yao, Qingzhi (Bangladesh Journal of Botany, 2023)
Pinus massoniana L. is an important andi typical ectomycorrhizal dependent tree species in Guizhou. In order to reveal the community structure and driving factors for ectomycorrhizal fungi (ECMF) of P. massoniana in Karst region, Illumina MiSeq high-throughput sequencing was used to study the diversities and community structure characteristics of ECMF in the rhizosphere soil of P. massoniana L. in the three sites of Xugongdian (SY1), Dishuiguanyin (SY2) and Yingtaowan (SY3) in Yuntai Mountain, Guizhou. The ectomycorrhizal fungi belonged to 2 phyla, 5 classes, 11 orders, and 38 genera. At the phylum level, ectomycorrhizal fungi mainly belonged to the Basidiomycota, accounting for 96.20% of all ectomycorrhizal fungi; the rest were Ascomycota fungi, accounting for only 3.8%. At the genus level, Russula, Cortinarius, Suillus, Inocybe, Tricholoma, Tomentella, Sebacina, Scleroderma, Cenococcum were the dominant ectomycorrhizal fungi of P. massoniana . The diversity and richness of ectomycorrhizal fungi communities in the three sites were significantly different. The ectomycorrhizal fungal community structures in SY1 and SY3 were similar, but were quite different from those in SY2. All soil factors explained 97.7% of the differences in the community composition of ECMF, with AP, TN, OM and AK being the main driving factors for the differences in the community composition of ectomycorrhizal fungi in the three sites. Bangladesh J. Bot. 51(4): 913-922, 2022 (December) Special